Performance and stability of jatropha (Jatropha curcas) for seed - RAIGER, H L; DUA, R P; SHARMA, S K; BHOGAT, B S (The Indian Journal of Agricultural Sciences, 2011)
This study was conducted during 2004–07 on 8 genotypes of jatropha (Jatropha curcas L.) at four locations for stabilizing productivity over seasons and regions. All the genotypes differed significantly in their seed yield in different environments. The environment (linear) and genotypes × environment (linear interaction) were also significant on the basis of stability analysis. The genotype ‘Chhatrapati’ can be successfully cultivated in plains as it gives higher seed yield (0.90 tonnes/ha), oil content (57.70%) and better stability (bi = 1.32, Sdi 2 = –0.09) for favourable environment. However ‘Hansraj’ gave higher seed yield (0.76 tonnes/ha) with better stability (bi = 1.05, Sdi 2 = –0.37) across the environments for seed yield.